Responses of Algal Cells to Engineered Nanoparticles Measured as Algal Cell Population, Chlorophyll a, and Lipid Peroxidation: Effect of Particle Size and Type. (17th September 2012) - Metzler, D. M.; Erdem, A.; Tseng, Y. H.; Huang, C. P.
Abstract : This paper investigated toxicity of three engineered nanoparticles (ENP), namely, Al2 O3, SiO2, and TiO2 to the unicellular green algae, exemplified by Pseudokirchneriella subcapitata with an emphasis on particle size. The changes in pH, cell counts, chlorophyll a, and lipid peroxidation were used to measure the responses of the algal species to ENP. The most toxic particle size was TiO2 at 42 nm with an EC20 of 5.2 mg/L and Al2 O3 at 14–18 nm with an EC20 of 5.1 mg/L. SiO2 was the least toxic with an EC20 of 318 mg/L. Toxicity was positively related to the surface charge of both ENP and algae. The chlorophyll content of the algal cells was influenced by the presence of ENP, which resulted in limited light and availability of nutrients due to increase in turbidity and nutrient adsorption onto the ENP surface, separately. Lipid peroxidation was attributed to reactive oxygen species (ROS). Fast reaction between algal cells and ROS due to direct contact between TiO2 and algal cells is an important factor for lipid peroxidation.